STRATEGI PENGEMBANGAN USAHA KERAJINAN TANGAN SABUT KELAPA DI LKP AKAS KABUPATEN KEBUMEN - Yunida Tri Andari; Lutfi Aris Sasongko; Eka Dewi Nurjayanti (MEDIAGRO, 2019)
Cocunut coir, as a secondary product of coconut, can be processed into eco-friendly fiber. This fiber is used as raw materials for handicrafts. This research aims to analyze the internal and external factors, as well as formulating an alternative strategy for the development of coconut coir handicraft business in LKP AKAS Kebumen Regency. The data used primary and secondary type. Data analysis method is done by using Internal Factors Evaluation (IFE) matrix, External Factors Evaluation (EFE) matrix, Internal External (IE) matrix and SWOT matrix. Data analysis resulted internal factors (strenghts) including abundant availability of raw materials, availability local labor, short marketing channels, national and international marketing. In the other hand, internal factors (weakness) are including lack of product innovation, an effective organizational structure, old manpower, an availability recorded orders, and lack of promotion through the website and social media. The external factors (opportunity) including the partnership with raw materials suppliers, the steadiness of raw material prices and repeated orders, the lack of competitors with the same materials, the supports from local government, and the request of delivery orders. In the other hand, the external factors (threaths) are including the risk of the market (numerous kind of handicraft with different materials), and the presence of other handicraft industry. The result of IE analysis, LKP AKAS is located in zone I, i.e grow and build. Suitable strategies for this area are market penetration, market development, and product development. Alternative strategies that can be done are: (1) make a business plan including production layout, product variation (production) and marketing to add customers; (2) summarize and manage the customer’s orders in order to have regular evaluation of the business progress in the future; (3) modified the product becomes more varied in order to be able to compete with other handicraft products; and (4) increase promotional activities online (website and social media) to attract consumers. Keywords : development strategy, handicraft, coconut coir, SWOT, Kebumen.